Analisis Produksi dan Pendapatan Usahatani Padi Pada Sistem Tanam Indeks Pertamanan (IP 200) di Kabupaten Toba - Purasa Siagian; Suswati Suswati; Siswa Panjang Hernossa (AGRIBIOS, 2026)
This study aims to analyze the production and income of lowland rice farming under the Cropping Index (CI) 200 system in Toba Regency. The research was conducted in Balige and Laguboti Sub-districts, where farmers cultivate rice twice a year. Two villages were selected from each sub-district, namely Bonandolok and Matio in Balige Sub-district, and Sitoluama and Pardinggaran in Laguboti Sub-district. The sampling method used in this study was purposive sampling, with the criterion that farmers have at least five years of farming experience. The total number of samples in this study was 96 lowland rice farmers who are members of farmer groups. The data analysis method employed was quantitative descriptive analysis. The results of the study indicate that, simultaneously, the use of production factors such as land area, seeds, urea fertilizer, NPK Phonska fertilizer, pesticides, and labor significantly affects rice production. Partially, land area and seeds have a significant effect on production, while urea fertilizer, NPK Phonska fertilizer, pesticides, and labor do not have a significant effect on rice production under the Cropping Index (CI) 200 system in Toba Regency. The average income of rice farming under the CI 200 system in Toba Regency is IDR 25,716,162, with an R/C ratio of 1.65, indicating that rice farming is profitable.